2021
DOI: 10.1111/exsy.12903
|View full text |Cite
|
Sign up to set email alerts
|

Expert system for detection of congestive heart failure using optimal wavelet and heart rate variability signals for wireless cloud‐based environment

Abstract: Congestive heart failure (CHF) is a cardiac disorder caused due to inefficient pumping of the heart, which leads to insufficient blood flow to the various parts of the body. The electrocardiogram (ECG) is widely used for the detection of heart diseases. However, it is prone to noise resulting in the detection of P, Q, R, S, and T waves ambiguous and erroneous. The heart rate variability (HRV) is considered to be a good indicator of various cardiac abnormalities. Hence, HRV is preferred. HRV can depict the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…One of the cases has been simulated assuming a compliant wall boundary condition. From existing literature (Canchi et al, 2018; Sharma et al, 2021), it has been observed that the aneurysm growth is due to wall thinning caused by the removal of SMC in the artery wall and it has been analysed using analytical calculations in both rest and exercise conditions. Since it is not possible to numerically predict the wall thinning and simulate the aneurysm growth, aneurysm has been built artificially near the bifurcation region, the variation in the flow pattern and the WSS in the aneurysm region was monitored for both rest and exercise condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the cases has been simulated assuming a compliant wall boundary condition. From existing literature (Canchi et al, 2018; Sharma et al, 2021), it has been observed that the aneurysm growth is due to wall thinning caused by the removal of SMC in the artery wall and it has been analysed using analytical calculations in both rest and exercise conditions. Since it is not possible to numerically predict the wall thinning and simulate the aneurysm growth, aneurysm has been built artificially near the bifurcation region, the variation in the flow pattern and the WSS in the aneurysm region was monitored for both rest and exercise condition.…”
Section: Methodsmentioning
confidence: 99%
“…Very limited literature is available to understand the effect of WSS in CA aneurysm in bifurcation region (rigid and compliant vessel) including dynamic growth of aneurysm in rest and exercise conditions and if such analysis is carried out it would be a good addition in systematic approach for pre-planning of necessary clinical interventions. There are some advanced expert systems exist in literature for automatic identification of cardiac related abnormalities (Sharma et al, 2021). In the present work, a CA model from clinical data with fusiform aneurysm in rigid and complaint condition has been developed and the effects of WSS in hemodynamic pattern near the bifurcation region in rest and exercise conditions using CFD is presented for early decision making.…”
mentioning
confidence: 99%
“…Machine learning algorithms have been widely used in different fields such as smart city applications (Tiwari et al, 2021), score prediction (Birant, 2021), medical diagnosis (Sharma et al, 2021), and fraud detection (Forough & Momtazi, 2022). Besides these topics, human activity recognition (HAR) is an emerging field, in which machine learning (ML) techniques are used to generate a classifier that learns activities from a set of observations of individuals' actions.…”
Section: Introductionmentioning
confidence: 99%
“…This process consumes time and requires sufficient expertise. To negate these, HPT is often detected using computational intelligence-based diagnostic techniques [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%